2022
DOI: 10.4236/jbm.2022.107001
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Predisposing Factors of Atherogenic Dyslipidemia in an Urban Pediatric Population in Cameroon

Abstract: Background: Dyslipidemia in childhood contributes to an increased risk of cardiovascular diseases later in life. This study sets out to determine the prevalence of dyslipidemia and describe the associations between selected variables and dyslipidemia in Cameroon urban children. Methods: This crosssectional hospital-based study included 415 children (188 boys and 227 girls) between the ages of 5 and 16 years. Dyslipidemia was defined as an abnormal value of one or more of the following lipids: Total cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Navti et al also suggested that increased BMI, waist circumference, and waist-to-height ratio were associated with lower HDL levels by increasing HDL-C catabolism due to insulin resistance, which suppresses lipolysis in an urban pediatric population in Cameroon [ 50 ]. Based on the current results, taller individuals exhibited decreased levels of HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Navti et al also suggested that increased BMI, waist circumference, and waist-to-height ratio were associated with lower HDL levels by increasing HDL-C catabolism due to insulin resistance, which suppresses lipolysis in an urban pediatric population in Cameroon [ 50 ]. Based on the current results, taller individuals exhibited decreased levels of HDL-C.…”
Section: Discussionmentioning
confidence: 99%